Effect of Coriander Oil (Coriandrum sativum) on Planktonic and Biofilm Cells of Acinetobacter baumannii - Duarte, Andreia (2020)
The increasing incidence of hospital-acquired infections caused by multi-drug resistant pathogens, such as Acinetobacter baumannii, coupled with the low efficacy of drugs and rising treatment costs has created interest in the potential antimicrobial properties of natural products. The main objective of this work was to determine the effect of coriander essential oil on Acinetobacter baumannii in different growth phases, as well as its ability to inhibit the formation or eradication of biofilms. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of coriander oil using a microdilution broth susceptibility assay was determined. The effects of different concentrations of coriander oil (ranging from 0.125 to 4×MIC) on biofilm formation and on established biofilm were tested using 96-well microtiter plates. Crystal violet assay was used as indicator of total biofilm biomass and the biofilm viability was assessed with a XTT staining method. It was found that coriander oil presented significant antibacterial activity against all tested strains of A. baumannii, with MIC values between 1 and 4 μL/mL. The MBC values were the same as the MIC, being an indicator of the bactericidal activity of this essential oil. In what concerns the effect of this essential oil on biofilm formation inhibition was observed of at least 85% of biomass formation by all A. baumannii strains using 2×MIC of coriander oil, in addition to a decrease in the metabolic activity of the cells. After exposure to coriander oil, a decrease in 24 h and 48 h-old biofilm biomass and metabolism was seen for all tested concentrations, even with sub-inhibitory concentrations. Coriander essential oil proved to have a significant antibacterial and anti-biofilm activity and should be considered in the development of future disinfectants to control A. baumannii dissemination.